IV. STORAGE AND GERMINATION TESTS ON SHOREA JAVANICA SEEDS - UMBOH, M.I.J. (BIOTROPIA, 2024)
SeedsÂ ofÂ ShoreaÂ javanicaÂ KÂ &Â VÂ (Dipterocarpaceae),Â wereÂ subjectedÂ toÂ differentÂ treatmentsÂ of temperature (27 Â± 2Â°C, 20 Â± 2Â°C and < 10Â°C), coating (ash and paraffin) and relative humidity (20, 66 and 86%) and their germination capability as well as moisture content assessed after 3, 7, 14 and 30 days of storage. The germination percentage ofÂ the seeds stored 30 daysÂ in aÂ cloth bag under differentÂ conditions of temperature showed highly significant differencesÂ (a = 0.01). No significant differences wereÂ found onÂ the effect of coating, duration of storage as well as on the interaction between these two factors. The moisture content of the seeds between 13 and 14% gave a germination percentage above 50% after 30 days.Â Â